2017
DOI: 10.1289/ehp442
|View full text |Cite
|
Sign up to set email alerts
|

Population-Level Exposure to Particulate Air Pollution during Active Travel: Planning for Low-Exposure, Health-Promoting Cities

Abstract: Background:Providing infrastructure and land uses to encourage active travel (i.e., bicycling and walking) are promising strategies for designing health-promoting cities. Population-level exposure to air pollution during active travel is understudied.Objectives:Our goals were a) to investigate population-level patterns in exposure during active travel, based on spatial estimates of bicycle traffic, pedestrian traffic, and particulate concentrations; and b) to assess how those exposure patterns are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…Based on spatial estimates of cyclists and pedestrians, traffic has been shown to be correlated with street functional class and proximity to high traffic roads. Also, it is seen that the highest rates of active travel are in neighborhoods with high levels of population density, land use mix, open space, and retail area (Hankey et al, 2017). Similarly, Mathews et al (2009) support that there are significant differences among gender and age when it comes to being physically active as well as the type, location, and purpose of the activity.…”
Section: Factors Affecting Active Transportationmentioning
confidence: 84%
See 1 more Smart Citation
“…Based on spatial estimates of cyclists and pedestrians, traffic has been shown to be correlated with street functional class and proximity to high traffic roads. Also, it is seen that the highest rates of active travel are in neighborhoods with high levels of population density, land use mix, open space, and retail area (Hankey et al, 2017). Similarly, Mathews et al (2009) support that there are significant differences among gender and age when it comes to being physically active as well as the type, location, and purpose of the activity.…”
Section: Factors Affecting Active Transportationmentioning
confidence: 84%
“…Also, cycling is the preferable commuting mode and specifically cycling is three times more likely to be chosen by males (Lawson et al, 2013a). Another factor that influences active transportation is population-level patterns (Hankey et al, 2017). Based on spatial estimates of cyclists and pedestrians, traffic has been shown to be correlated with street functional class and proximity to high traffic roads.…”
Section: Factors Affecting Active Transportationmentioning
confidence: 99%
“…Furthermore, LUR models can give valuable information for public health officials and urban planners to reduce population exposure to air pollution and design health-promoting cities with less polluted routes for pedestrian and cyclists. For instance, Hankey S et al 2016 [21] combined facility-demand and LUR models to highlight exposure patterns during active travel suggesting that it should be possible to reduce exposure by~15% after intervening on the given scenario. Recently, several studies confirmed that the health benefits linked to active travel outweigh the risks such as exposure to air pollution or accidents, suggesting that the attempt to build more walkable and bikeable urban environments is worth the effort [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Due to an increase in low-cost sensing for air pollution monitoring, the real-time strategies for exposure control in cities have been further developed (Kumar et al, 2015). Crowdsourced monitoring that enables citizens to produce geospatial data is constantly growing and shows considerable potential (Heipke, 2010). Large and diverse groups of people who lack formal training can easily describe their environments with a mobile phone or smartphone and upload data via informal social networks and web technology.…”
mentioning
confidence: 99%